Chordoma of the thoracic spine - Case report - Topsakal, C; Bulut, S; Erol, FS; Ozercan, I; Yildirim, H (Japan Neurosurgical Soc, 2002)
A 44-year-old woman presented with a thoracic chordoma with intrathoracic extension manifesting as complaints of lower extremity weakness, hypesthesia below the levels of T5-6, and sphincter incontinence. Almost total resection combined with anterior interbody fusion and stabilization was possible through a left transpleural transthoracic approach. She suffered recurrence after 2 years and was considered inoperable. Biopsy revealed a malignant chordoma with no sarcomatous differentiation. Chordoma is an uncommon malignant bone tumor originating from remnants of the embryonal notochord, occurring mostly along the axial skeleton, at the extremity of the vertebral spine, and is least common in the thoracic region. Differential diagnosis is problematic and biopsy is helpful particularly if considered inoperable. Thoracic chordomas of the malignant type manifest as cord or root compression. Classical malignant chordomas must be distinguished from chondroid, benign, or other types of chordomas, since the biological behavior and clinical features are distinct. However, the differential diagnosis cannot be based on histological examination, but long-term follow up is required. Most patients have extradural and intraspinal tissue extension at the time of diagnosis, which makes complete resection impossible. Aggressive surgery without violation of surgical borders is the best choice in the treatment of thoracic chordoma. Thoracic chordoma is a recurring neoplasm and is prone to dissemination and sarcomatous differentiation despite its slow-growing nature.
Keywords: chordoma; notochord; physaliphorous cell; thoracic spine